Second Caribbean Ministerial Safe School Forum: Education Sector Resilience: Exploring the Possibilities, 29 and 30 April 2019, Saint Vincent and the Grenadines: Forum Report - Global Alliance for Disaster Risk Reduction and Resilliance in the Education Sector (Global Alliance for Disaster Risk Reduction and Resilliance in the Education Sector, 2019)
The Second Caribbean Safe School Ministerial Forum on School Safety is a follow-up of the Forum held in April 2017, adding to a collaborative and coordinated approach among actors of the region’s education sector. It contributed to the Regional Comprehensive Disaster Management (CDM) Strategy and Programming Framework 2014-2024 of CDEMA; Worldwide Initiative for Safe Schools (WISS) by UNDRR; Caribbean Safe School Initiative; the Samoa Action Plan for SIDS, the Global Action Program on Education for Sustainable Development; the Sendai Framework for Disaster Risk Reduction 2015-2030, the Paris Agreement on climate change and to the 2030 Agenda for Sustainable Development. The forum focused on the following objectives: a) To update the Caribbean Regional Roadmap on Schools Safety, b) To facilitate sign on to the Antigua and Barbuda Declaration on Schools Safety and Regional Roadmap Implementation by new members, c) To monitor progress and achievements in the implementation of the Caribbean Regional Roadmap on Schools Safety, d) To promote and raise awareness of the World Initiative on Safe Schools and the Caribbean Schools Safety Initiative, e) To promote the engagement of Youth in the CSSI, f) To facilitate a ministerial dialogue with donors on support for the Caribbean Safe Schools Initiative.
Keywords: school safety